Electrochemical DNA biosensor based on iron oxide/nanocellulose crystalline for detection of Mycobacterium tuberculosis - Che Engku Chik, Che Engku Noramalina (2017)
In this study, electrochemical DNA biosensor based on carboxyl functionalized iron oxide/nanocellulose crystalline surface modified with cetyl trymethylammonium bromide (COOH-Fe3O4/NCC/CTAB) for detection of Mycobacterium tuberculosis (MTB) was developed. The modification was made by drop coating a carboxyl COOH-Fe3O4 nanocomposite with NCC/CTAB on surface of screen printed carbon electrode (SPCE). The modified SPCE was electrochemically characterized using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) in the present of Fe(CN)63/4- as electrolyte. The electrochemical characterization confirmed the high rate of electron transfer, was due to increase of electroactive surface area and excellent conductivity of modified SPCE. The optimization of SPCE modified in term of COOH-Fe3O4 concentration, volume/volume ratio of COOH-Fe3O4:NCC/CTAB and scan rate was achieved by 0.5 mg/ml, 1:1 ratio and 100 mV/s; respectively. The present of functional groups were confirmed by physical characterization using fourier transform infrared spectroscopy (FTIR), the surface morphology was confirmed by field emission scanning electron microscopy (FE-SEM), and the elemental composition of modified SPCE was confirmed by energy dispersive X-ray spectroscopy (EDX). The deposition of modifier materials on the surface of SPCE was properly characterized through physical characterization. Their electrochemical activities and sensing capability towards detection of Mycobacterium tuberculosis (MTB) was investigated using differential pulse voltammetry (DPV). Ruthenium complex bipyridyl Ru(bpy)32+ was used as redox indicator in monitoring hybridization events of the DNA. A 5’-NH2- end of DNA probe was used to form a covalent bond of amide bond immobilized with carboxyl group via ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide EDC/NHS as coupling mechanism. The selectivity of the fabricated DNA sensor was confirmed by the different signal produced by Ru(bpy)32+ in differentiate ssDNA probe, dsDNA target complementary, non-complementary and the mismatch DNA sequences. The optimum condition were obtained using the following criteria such as Tris EDTA as supporting electrolyte pH 8, deposition potential (0.3V), deposition time (5 sec) probe DNA concentration, immobilization time (60 minutes), EDC/NHSS immersion, ionic strength (20 mM), hybridization time (35 minutes at 42oC) and Ru(bpy)3 2+ concentration (25 μM). Performance of the biosensor was investigated using different concentration of DNA target in the range of 1.0 x 10-12 to 1.0 x 10-6 M and the limit of detection was calculated to be at 7.96 x 10-13 M. The calibration curve showed a linear relationship with equation, y=0.6936 log (x) + 11.47 and correlation coefficient of R2=0.9896. DNA of MTB was extracted from clinical sample and underwent PCR procedure for real sample analysis. The developed biosensor was demonstrated the difference between positive and negative MTB sample, mycobacterium other than tuberculosis (MOTT) and respiratory- related bacterial samples, Staphyloccocus aureus and confirmed that this fabricated electrochemical DNA sensor have good selectivity and effectively detected the sequence of DNA from MTB using PCR product analysis. The studied of stability and reproducibility showed a satisfactory result with loss only 5.87% activity after 7 days and below 50% after 5 weeks and finally the reproducibility value of 3.87% (n=8). The repeatability showed quite high with value of 29.30% indicating to a good SPCE to be used for TB detection if compared to previous study.